Recovery of plant diversity and soil nutrients during stand development in subtropical forests of Mizoram, Northeast India - SH B SINGH; B P MISHRA; S K TRIPATHI (Biodiversitas Journal of Biological Diversity, 2015)
Singh ShB, Mishra BP, Tripathi SK. 2015. Recovery of plant diversity and soil nutrients during stand development insubtropical forests of Mizoram, Northeast India. Biodiversitas 16: 205-212. The present study assessed the recovery of tree speciesdiversity and soil nutrient dynamics with stand development in subtropical semi-evergreen forest of Mizoram. The study was carried outin two regenerating forest stands following disturbance and one undisturbed forest. Schima wallichii was the dominant species in allstands showing IVI of 63.8, 83.3 and 75.9 in undisturbed, moderately disturbed and highly disturbed stands, respectively. Castanopsistribuloides was co-dominant species in the undisturbed and the moderately disturbed but this species was replaced by Sterculia villosa inthe highly disturbed stand. The shift in position of species and families from undisturbed to highly disturbed stands could be linked withdegree of disturbance. Log-normal dominance-distribution curves in the undisturbed and moderately disturbed stand indicating thestability of community, while short hooked curve in the highly disturbed stand indicates unstable nature of the community. The soilproperties (organic C, total nitrogen, and available phosphorus) increased significantly during the course of stand development, whereas,decrease with the depth in these forest stands.